Visuomotor functions of the posterior parietal cortex. - Jackson, SR; Husain, M (2006)
In this special issue of Neuropsychologia leading experts in the field discuss controversies and advances in the role of the posterior parietal cortex (PPC) in visuomotor control. The papers are wide-ranging in their scope, covering monkey physiology and anatomy, functional imaging in humans and monkeys as well as transcranial magnetic stimulation and lesion studies in humans. The collection provides an important overview of the current state-of the-art in this area of research, including discussions on homologies between monkey and human parietal regions, the role of co-ordinate transformations and intermediate representations from vision to action, and reviews of controversial hot topics in this field.